Enhancing communication and behavioral skills in Spanish-speaking children with autism spectrum disorder using SymboTalk and EC+: A pilot study - Zurita-Díaz, Antonio Javier; Calleja-Reina, Marina (Elsevier, 2025)
- Introduction: Autism spectrum disorder (ASD) is a neurological condition that impacts receptive and expressive communication as well as behavior. In this context, augmentative and alternative communication (AAC) strategies are increasingly integrated with information and communication technologies (ICT). ICT supports have significantly advanced AAC interventions, incorporating tools, software, and digital apps to facilitate information processing in educational and therapeutic settings. Despite the benefits, the wide range of these supports raises concerns about proper usage and optimal alignment with specific needs. - Method: This pilot study evaluated the impact of an intervention with two different AAC with assistance (AAC+a) on 40 participants with ASD Level 3 within a Spanish-speaking context: communication board from the SymboTalk platform and list-form from the multimodal EC+ app. These supports were implemented using the aided augmented input strategy, an intervention methodology that utilizes these supports to facilitate functional communication by combining visual and oral input. - Results: After 16 weeks, significant improvements in expressive and receptive communication were observed using the communication board support, although the other resource also proved to be a favorable support for the intervention. No differences were found between groups in behavioral outcomes and modes of communication. - Conclusions: The results highlight the effectiveness of these supports, emphasizing the importance of teaching communication skills and implementing this strategy in a Spanish-speaking context. This consideration is crucial given the unique characteristics of this context and its potential impact on children with ASD and complex communication needs.
Mejorando las habilidades comunicativas y conductuales en niños de habla española con trastorno del espectro autista utilizando SymboTalk y EC+: Un estudio piloto
Este manuscrito es la versión aceptada (postprint) del artículo publicado en la Revista de Logopedia, Foniatría y Audiología. https://openpolicyfinder.jisc.ac.uk/id/publication/17746
Keywords: Trastornos del espectro autista en niños - Innovaciones tecnológicas; Autism spectrum disorder; Aided augmented input; Augmentative and alternative communication; Information and communication technologies; Technology